Estudo teórico da influência da adição de adesivante nas propriedades físico-quimicas do polipropileno reforçado com fibras de vidro - Sena, Sthefany dos Santos (Universidade Federal de São Carlos, 2023)
Fiber-reinforced polymeric composites are widely used today, being applied in several areas such as aeronautics, automotive, military, medical, among others. However, some polymers present low adhesion in the interfacial region with the glass fiber due to the polarity of the chains. In order to improve this property, adhesive molecules can be added to the system, which can increase the surface polarity of the silica, the polymer or both. In this work the adhesive molecules were bonded to the polymer molecule. The polymer studied was polypropylene with and without addition of maleic anhydride, in addition to modification of the silica surface, with and without hydroxyls. The molecular dynamics method was used to study the effects of these modifications, as well as the change in behavior when the system is subjected to a mechanical test. It was found that the systems containing the modified polymer did not suffer detachment from the silica because the adhesion was more efficient, showing that increasing the polarity of the chains through the addition of adhesive agents is effective. In addition, the umbrella sampling method was used to calculate the adhesion free energy. It was possible to observe that there is a significant difference between the system with and without coupling agent, with better interfacial adhesion for the first case. In addition, the silica that had hydroxyls on the surface together with pure polypropylene showed a free energy of adhesion very similar to the system that contained the coupling agent but the silica did not contain terminal hydroxyls. On the other hand, the system that had the two possible modifications, coupling agent and hydroxyls in the silica, presented the best adhesion performance, justified by the intermolecular interactions that could occur in the interfacial region. This result corroborates the tensile test, where this system showed an improved behavior in the formation of voids in the polymeric matrix compared to the system MAPP-SiO2.
Theoretical study of coupling agent addition influence on the physical and chemical properties of glass fiber-reinforced polypropylene
Keywords: Dinâmica molecular; Compósitos; Polímeros; Polipropileno; Fibras de vidro; CIENCIAS EXATAS E DA TERRA::QUIMICA